Negotiating Meaning and Sensitivity: Translating Awliya, Jihad, and Kafir in the Indonesian Qur’an Translation by the Ministry of Religious Affairs - Trisno Susilo; Riza Tamami; Moh Abdul Kholiq Hasan (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This article aims to analyze the dynamics of the translation of the terms awliya, jihad, and kafir in the 2002 and 2019 editions of the Ministry of Religion's Al-Quran Translation. This study highlights the changing meaning and strategy of translation in response to Indonesia's social and political context. The main focus is directed at the theological and social implications of the choice of translation diction. Theoretical framework: This study uses Quranic semantics, contextual interpretation, and Qur'anic translation theory as an analytical framework. Quranic semantics maps the field of meaning of terms, contextual interpretation emphasizes historical and contemporary contexts, while translation theory assesses the strategy of translation of meaning. All three are used integratively to read the relationship between text and context. Literature review: Previous studies of the translation of the Qur'an in Indonesia have generally dealt with linguistic or historical aspects separately. Comparative studies across editions of official translations with a focus on sensitive terms are still limited. This article fills this gap by systematically linking linguistic analysis, interpretation, and social dynamics. Methods: This study uses a descriptive qualitative approach based on literature studies. The data was analyzed through searching for verses containing the terms awliya, jihad, and kafir in the 2002 and 2019 editions of the translation. The analysis was carried out using semantic approaches, contextual interpretation, and translation theory. Results: There is a shift in translation from a literal approach to a contextual and moderate approach. The term awliya is interpreted more relationally, jihad is contextually explained to prevent violence, and kafir is recontextualized to "disobedient" or "kufr". These changes reflect the response to Indonesia's social sensitivities. Implications: Theoretically, these findings confirm the translation of the Qur'an as a dynamic and contextual practice of interpretation. In practical terms, this study supports the development of more accurate and moderate translations. Another implication is the strengthening of religious moderation and harmonization between religious communities. Novelty: The novelty of this article lies in a comparative analysis across the official translation editions of the Ministry of Religion. The focus on three sensitive Quranic terms, combined with Indonesia's socio-political context. Integrative approaches to semantics, interpretation, and translation are the main methodological contributions.